HIRARC METHOD APPROACH AS ANALYSIS TOOLS IN FORMINGOCCUPATIONAL SAFETY HEALTH MANAGEMENT AND CULTURE - Eka Rakhmat Kabul; Farid Yafi (Universitas Padjadjaran, 2022)
The purpose of this study is to observe and analyze the potential hazards that can cause accidents in the activity of lifting building materials using Tower Crane on a construction project. The method used in this research is Hazard Identification, Risk Assessment and Risk Control (HIRARC). By using this method, it is hoped that it can reduce the number of accidents that occur, find out the causes of accidents, and establish control measures. The results of the study indicate that there are 11 risks in activities that have the potential to cause accidents. Where 2 risks have an “Extreme” level of danger, namely an accident with more than one person and the status is “Urgent” so that it needs immediate treatment, 4 risks are classified as “High” which need serious attention and 2 risks are “Medium” which requires special attention. The conclusion of the research is that companies must establish and maintain procedures to carry out hazard identification, risk assessment, and risk control as needed by removing water in the basement, grinding protective pairs, using earplugs, making SOPs, using scaffolding, installing covers holes, put up warning signs, cut metal out of the floor, used personnel protective equipment (PPE), and provided a first aid kit. It is recommended that the company immediately recruit HSE experts on each project so that the company’s Quality Health Safety Environment (QHSE) Department only receives reports and proposals which will later be used as SOPs for the next construction project.